A revision on the effect of FDI on inequality-adjusted human development index - Cao, Thi Hong Vinh; Nguyễn, Thị Ngân Hà; Pham, Hong Dien (Journal of International Economics and Management, 2018)
Inequality-adjusted Human Development Index (IHDI) is a new measurement of human development (HD) designed by the UNDP which addresses a renowned shortcoming of the previously used Human Development Index (HDI), which is inequality in distribution of human development achievements. Despite its advantages, this new approach has not been fully integrated into studies relating to the human development field, especially as far as FDI is concerned. FDI is an important factor affecting human development. Studies on the impact of these financial inflows on human development have only used HDI as a HD proxy. Using a panel data of 106 countries from the database of World Bank over the period of 2010 - 2015, our paper offers new understanding on how FDI affects HD with inequality being taken care of using IHDI. We find that FDI significantly and negatively affects human development. When samples of countries separated by continents are taken into account, the effects of FDI are different. Institutional quality index is found to have no notable contribution to human development. Several sub-indices, however, do positively and significantly affect human development. Regarding inequality, our findings confirm that FDI inflows widen the gaps in income, especially among countries in Asia. Regarding different aspects of IHDI, FDI contributes to increase life expectancy but reduce income of people in Latin America and Caribbe.